Case Report: Histological Transformation to Atypical Carcinoid in RET Fusion-positive NSCLC Following Immune Therapy Resistance - Yu ZHANG; Hui ZHANG; Wei ZHONG; Minjiang CHEN; Mengzhao WANG (Chinese Journal of Lung Cancer)
Immune checkpoint inhibitors (ICIs) have become the cornerstone of treatment for driver gene-negative advanced non-small cell lung cancer (NSCLC). However, resistance is inevitable, and the underlying mechanisms remain incompletely understood. Histological transformation is a rare but emerging cause of acquired resistance to immunotherapy, with only sporadic case reports documented to date. Here, we report the first case of lung adenocarcinoma that underwent histological transformation to atypical carcinoid following first-line therapy with ICIs combined with chemotherapy, highlighting the critical role of histological lineage switching in mediating NSCLC resistance to ICIs. Notably, the patient harbored a rearranged during transfection (RET) fusion mutation. Subsequent targeted therapy with Selpercatinib after histological transformation demonstrated favorable efficacy, suggesting a potential therapeutic strategy for atypical carcinoid patients with co-occurring rare driver mutations. This case provides a potential therapeutic option for atypical carcinoid patients with rare mutations.